Analisis Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Perusahaan (Studi Empiris Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2012-2016) - Aida Nahar; Weni Purwanti (Accounting Study Program, Faculty of Economics and Business, 2017)
The company's financial performance has important meaning for various parties. By knowing the financial performance of a company will be able to know the financial condition of the company. Return on Assets profitability ratio is used to measure the company's financial performance. The purpose of this study was to determine and analyze the effect of Current Ratio, Cash Turn Over, Debt to Asset Ratio, Debt to Equity Ratio, Inventory Turn Over, and Total Asset Turn Over partially and simultaneously on the financial performance of companies listed in the Jakarta Islamic Index ( JII) period 2012-2016 as many as 13 companies. This type of research data is quantitative data. The results of this study partially show that the Inventory Turn Over and Total Asset Turn Over variables have a positive and significant effect on Return On Assets. The variable Debt to Asset Ratio has a negative and significant effect on Return On Assets. Variable Current Ratio, Cash Turn Over, and Debt to Equity Ratio have no effect on Return On Assets. And simultaneously the variables of Current Ratio, Cash Turn Over, Debt to Asset Ratio, Debt to Equity Ratio, Inventory Turn Over, and Total Asset Turn Over have a simultaneous and significant effect on Return On Assets.